Effects of L. casei strain Shirota supplementation on fecal profiles and body weight status of school children - Saipudin, Nurul Ain (2017)
The concentration of short-chain fatty acids (SCFAs) may be disrupted in overweight and obese children. The effect of probiotic Lactobacillus casei strain Shirota (LcS) on the fecal SCFAs concentration is still unclear. The purpose of this intervention was to investigate the effect of LcS on fecal SCFAs and body weight status in school children. Using the crossover study design, LcS was provided for 4-weeks with 4-weeks washout period to the children aged 7 to 10 years old. A total of 22 overweight and obese (OWOB) with mean age = 8.73 ± 1.03 years old; BMI = 24.73 ± 3.91 kg/m2 kg/m2 and 55 % boys participated and randomly divided either to intervention or control group. This study recruited normal weight children (NW, n= 20) as a comparison with the OWOB on the fecal profiles and body weight. During the intervention period, the participants received daily 80 ml of probiotic drink at a dosage of 3.0 x 1010 colony-forming unit (CFU) for 4-weeks. The primary outcome measures were fecal SCFAs concentration and body weight status of the children. Other outcome measures included dietary intakes, physical activity level and fecal consistency. At baseline data of all participants, the concentration of propionate (Mean=43.08 μmol/g; SD= 37.14) was the highest; followed by acetate (Mean= 29.73 μmol/g; SD= 23.30) and butyrate (Mean= 23.19 μmol/g; SD= 17.75) with OWOB reported a higher concentration of butyrate (52%) and propionate (38%) as compared to NW participants (p>0.05). After 4-weeks of the LcS supplementations, the propionate and the total SCFAs concentration increased significantly than the baseline concentration (p<0.05). The fecal propionate concentration increased by 161 % and total SCFAs concentration increased significantly by 79% from the baseline in the OWOB participants. Meanwhile, the fecal propionate and total SCFAs concentration of the NW participants in the intervention group had increased significantly by 178 % and 79% respectively at the end of supplementations (p<0.05). The study also found a significant difference in fecal propionate and total SCFAs of the intervention group in OWOB and NW (p<0.05). With regards to the body weight, the mean percentage of body weight change was also significantly increased by 6.4% in OWOB and 7.5% in NW participants at the end of supplementations (p<0.05). No significant changes in dietary intakes and physical activity levels of the participants throughout the study (p>0.05). In conclusion, the increased in SCFAs mainly propionic acid after supplementing with a probiotic containing LcS may explain its potential as an appetite suppressor. Nevertheless, whether the effect on appetite may translate to weight control in the future warrants future investigationAbstract of thesis presented to the Senate of Universiti Putra Malaysia in fulfilment of the requirement for the degree of Master of Science.